PROSPECTS OF APPLYING MARKETING STRATEGIES IN THE DEVELOPMENT OF THE COUNTRY’S TOURISM MARKET (IN THE CASE OF THE TOURISM MARKET OF UZBEKISTAN) - Erkinova Nilufar (Scholar Express Journals, 2022)
This article describes ways to increase the role of tourism in the country’s economy and its share in its development, and at the same time implement strategic measures in the field of tourism marketing in order to ensure sustainable development in the country’s tourism market. Also, the analysis of the imbalances that have occurred in certain sectors of the tourism market of Uzbekistan is considered and their elimination, as well as finding and expanding the target audience, as well as attracting consumers in the tourism industry and meeting their needs at the level of demand, are targeted marketing strategies for the effect of use is revealed
Keywords: Marketing strategies; tourism marketing; market of tourism; goals of visits